Kajian Semiotika Charles Sanders Pierce Karya Lukis Erica Hestu Wahyuni “Vacation in Prosperity Land” - Areel Nindan Ajeng (Fakultas Ilmu Budaya, Universitas Brawijaya, 2021)
Painting is a two-dimensional art consisting of lines, fields, shapes and colors. Painting works are made not without reason, artists create works often for expression as well as expressing ideas and creativity. In addition, there are many values contained in art. This article discusses the meanings contained in the painting “Vacation in Prosperity Land” by Erica Hestu Wahyuni. This work is a work that explains how happy the world of children is, which is not full of falsehoods. The review in this work was conducted to prove the correlation between visual and its meaning, so that it can become a medium of information. The results of the semiotic study in this painting show that there are visuals and color compositions that show that Erica has succeeded in elevating something complex into a simple thing.